PENGGUNAAN METODE READ ALOUD DALAM MEMBANTU KESULITAN BELAJAR DISLEKSIA TERHADAP SISWA - Muchlinarwati Muchlinarwati (Jurnal Pendidikan Nusantara, 2024)
Learning is a process of teaching and learning  activities and plays a role  in determining student success. From  this learning  there  will be a reciprocal activity  between teachers and students to achieve better goals. This research aims to enhance storytelling ability implemented by Read Aloud method. This is a classroom action research (CAR). It consist of two cycles. Each cycle conducted of four phase, namely planning, action, observation, and reflection. Data collection technique conducted by observation, interview, documentation, field note, and performance test. The data validity test were source triangulation and method triangulation. It used descriptive comparative and critical analytic as data analysis. The result  indicated  that  the  implementation  of  Read  Aloud  method  could  be  able  to enchance the storytelling ability and also the effectiveness of learning study PAI.